Enhancing Teachers’ Creativity with an Innovative Training Model and Knowledge Management - Vesna Skrbinjek; Maja Vičič Krabonja; Boris Aberšek; Andrej Flogie (Education Sciences)
In the post-COVID-19 era, education requires teachers to engage learners across diverse learning environments (at school or other formal institutions, at home, outdoors, or in virtual environments) using innovative learning strategies. To meet these challenges, teachers must upskill their creativity and strengthen their pedagogical digital competencies and knowledge management skills. This study introduces the innovative teacher training and support (TTS-IPCD) model to enhance teachers’ creativity and pedagogical digital competencies. This research involved a sample of 350 teachers from 75 primary and secondary schools over a four-year period. Teachers’ creativity was measured using the Kirton Adaption–Innovation Inventory (KAI), assessing key metrics such as problem-solving flexibility, openness to change, and inclination toward novel approaches. Quantitative analysis was conducted using an independent samples t-test to evaluate teacher creativity changes. The results indicated that the TTS-IPCD model enhanced teacher creativity in the direction of a stronger propensity toward innovative behaviors, including embracing diversity and change in their work, solving problems through novel approaches, and adopting a holistic perspective rather than strictly adhering to established routines. Furthermore, the TTS-IPCD model improved teamwork and collaboration, contributing to the development of more adaptive and innovative learning environments. These findings highlight the importance of continuous professional development of teachers focused on creative pedagogy and digital competencies to equip teachers for the evolving educational landscape.